Nirguna Bhakti in Eastern India : Ideology, Identity and Resistance - Nath, Dambarudhar (Brill | Manohar Publishers & Distributors, 2024)
Like in other parts of India, the Bhakti movement also spread into the eastern regions in the early sixteenth century, and had brought a large section of the people under its banner stretching from Koch Behar in the west in North Bengal to the foothills of Arunachal Pradesh in the eastern frontier. The present work is a comprehensive, but a critical history of the growth and development of the mystical movement in this part of India from the early sixteenth to seventeenth century with special reference to the Māyāmarā sect, which claims to be nirguna in its essence, teachings, social ideology, and political influence. While doing this, the book has re-examined the theory that bhakti movement ultimately failed to usher in a democratic outlook and egalitarian aspects as it had originally proposed, and that it had ultimately submitted to the strong and dominant conservative forces. With a detailed and sceptical examination of the ideological and philosophical aspects of Sankaradeva, the founder of Bhakti movement in the eastern part of India, the work proceeds on to examine the historical situation behind the emergence of the radical branch of the movement, and its social and political implications. It shows how within every conservative structure, there remains a radical force which always carries on the forces of reform, resistance, and protest against the dominant ideology, if necessary even by adoption of militant methods. The emergence of the Māyāmarā sect from within the bhakti ideology, its role in the making of the society, and a militant resistant movement against the dominant class form the crux of the present work. While doing this, it has questioned many of the existing ideas and concepts about the movement, particularly, in this part of India.